EFL Students' Attitude Towards English Lessons Through Indonesia’s Merdeka Curriculum - Sitohang, Caecilia Adinda Rosa; Tarigan, Karisma Erikson; Ginting, Fiber Yun (ELT Worldwide: Journal of English Language Teaching, 2023)
The purpose of this study was to examine the attitudes of students towards English lessons within the context of the Merdeka curriculum. Specifically, the study aimed to investigate the impact of the Merdeka curriculum on students' attitudes towards English lessons, as well as identify the factors that contribute to students' positive attitudes towards the Merdeka curriculum at SMA Swasta Katolik Tri Sakti Medan. The analysis of qualitative data revealed that students exhibited favorable attitudes towards English lessons within the Merdeka curriculum. Specifically, in the cognitive component, the findings indicated that 62% of students held positive attitudes, 18% held negative attitudes, and 20% remained neutral. In the affective component, 53% of students displayed positive attitudes, while 22% exhibited negative attitudes and 25% maintained a neutral stance. Lastly, the conative component demonstrated that 59% of students showcased positive attitudes, 14% displayed negative attitudes, and 27% remained neutral. The present study employed qualitative data collection methods. The findings indicated that a majority of the student population, specifically 146 out of 197 students, expressed contentment in their English language learning endeavors. It was observed that certain factors contributed to the cultivation of positive attitudes among students towards English lessons. Firstly, students exhibited a preference for English lessons. Additionally, the presence of an engaging, knowledgeable, and perceptive subject teacher played a crucial role in creating an enjoyable learning environment. The impact of pupils' positive attitudes on their learning achievements is significant.